(3cJGH aj GdJGQjNs
(3ChdgG (B:s
(3abO CWGY Gddg hbGd QShd Gddg Udi Gddg Ydjg hSde (B: (3MjGJi NjQ dce heeGJi NjQ dce s
(3BNQgG (B:s
(3Ef eKdce ceKd hQb HdG Thc Edi SHYeGFI SfI , Ke Jchf CeJi HYO Pdc Thc HdG hQb , hEf JQcJge dGjJQchc , hEf aQQJ efge LPHhc , dGJQi ajge EdG SdWGf LGFQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jUd gPG GdcJGH ai JSLjdg dCNHGQ GdCfOdS Edi SfI (B665s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs